Proyecto para la implementación de un sistema de transporte turístico que interconecte las principales comunidades costeras y playas de las provincias de Manabí y Santa Elena - Arboleda Castro, Lorena Vanesa (2009)
As time passes by, Tourism is becoming one of the most important sectors for the economies of the countries, due to its direct impact in national development, revenues redistribution, balance of payments, employment, gross domestic product and regional economies. Taking this as a background, several reasons gave place “La Ruta del Sol” to reach a touristic peak in the last decade: paradisiacal landscapes; socio-natural locations where most antique Ecuadorian Pre-Ceramic period cultures set up; tourist resorts highly visited by adventure and water sports lovers; original marine mammals and migratory birds sightseeing sites; and its gastronomy. However, irresponsible government management has caused road deteriorations between communities/towns and Manabí province. The following written has as primal objective to measure de feasibility of establishing an alternate or nonconventional transport system, having as its main reason the improvement of mobilization between “La Ruta del Sol” surrounding spots so as to take advantage of its touristic potential. In order to achieve this, several studies will be run such as: marketing, technical, financial, and cost volume profit (sensitivity) analysis. Finally, a conclusion and recommendations will be presented at the end of this written.